2017
DOI: 10.1371/journal.pone.0175823
|View full text |Cite
|
Sign up to set email alerts
|

The electrical heart axis and ST events in fetal monitoring: A post-hoc analysis following a multicentre randomised controlled trial

Abstract: ObjectiveReducing perinatal morbidity and mortality is one of the major challenges in modern health care. Analysing the ST segment of the fetal electrocardiogram was thought to be the breakthrough in fetal monitoring during labour. However, its implementation in clinical practice yields many false alarms and ST monitoring is highly dependent on cardiotocogram assessment, limiting its value for the prediction of fetal distress during labour. This study aims to evaluate the relation between physiological variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Fetuses in cephalic, transverse, or breech position would give different ECG morphology. We have shown in a previous study ( 31 ) that a different fetal orientation, or a different orientation of the electrical heart axis with respect to the abdominal electrodes, affects the degree of ST elevation and as such might affect ST alarms triggered on an obstetrical ward. Normalization for the fetal orientation would be possible by using ultrasound imaging ( 30 ) or different (i.e., relative) ST alarm mechanisms ( 32 ).…”
Section: Discussionmentioning
confidence: 96%
“…Fetuses in cephalic, transverse, or breech position would give different ECG morphology. We have shown in a previous study ( 31 ) that a different fetal orientation, or a different orientation of the electrical heart axis with respect to the abdominal electrodes, affects the degree of ST elevation and as such might affect ST alarms triggered on an obstetrical ward. Normalization for the fetal orientation would be possible by using ultrasound imaging ( 30 ) or different (i.e., relative) ST alarm mechanisms ( 32 ).…”
Section: Discussionmentioning
confidence: 96%
“…The relation between the orientation of the electrical heart axis and the orientation of the scalp electrode yields different T/QRS baseline values, due to differences in ECG morphology. We found that fetuses with a higher T/QRS baseline are more prone to ST events, independent of the fetal condition [ 22 ]. In contrast, we found that fetuses with a lower T/QRS baseline are less prone to exceed the threshold for a ST event.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that variation in the orientation of the electrical heart axis between foetuses causes different T/QRS baseline values. Foetuses with a higher T/QRS baseline value were shown to be more prone to false positive ST events [26,27]. Multi-lead NI-fECG recordings can deliver a 12-lead foetal ECG, taking information on the orientation of the electrical heart axis, derived from ultrasound evaluation, into account.…”
Section: Discussionmentioning
confidence: 99%